The phenomenon of labelling in Polish schools in the context of children with migration experience in Poland - Marzena Sylwia Kruk (Journal of Modern Science)
Objectives The aim of this article is to answer the question about the occurrence of the labelling phenomenon in Polish schools in the situation of admitting refugee children to Polish educational institutions.